Comparison of oxysilver nitrate and oxysilver bisulfate, Part I: Synthesis and physicochemical properties. (15th October 2015) - Nadworny, Patricia; Omotoso, Oladipo; Zheng, Zhaoyan
Graphical abstract: Oxysilver nitrate (OSN) and oxysilver bisulfate (OSBS), prepared through ozonolysis, were compared to oxysilver compound (OSC) made by inorganic chemical synthesis using XRD, SEM, EA, CV, DSC/TGA, UV–Vis, and XPS. OSC contained some OSN but mostly OSBS. OSN and OSBS behavior in solution and storage is explored. Stability ranking: OSN > OSBS > OSC. Abstract: Multivalent silver complexes of oxysilver nitrate (OSN) and oxysilver bisulfate (OSBS) were prepared with excellent purity and yield through ozone oxidation of AgNO3 or Ag2 SO4 solutions, respectively. An inorganic chemical synthesis method for making oxysilver nitrate was also used to generate material (OSC) for comparison of the methods. The complexes were characterized with X-ray diffraction (XRD), scanning electron microscopy (SEM), elemental analyses (EA), cyclic voltammetry (CV), and X-ray photoelectron spectroscopy (XPS). The XRD structural refinement for OSBS is presented here for the first time. SEM showed that OSBS had significantly larger particles than OSN or OSC. Through a comparison of OSBS, OSN, and OSC using the XRD, XPS, EA and also differential scanning calorimetry (DSC) data, it was discovered that the OSC was actually a mixture of oxysilver nitrate and oxysilver bisulfate, meaning that the inorganic chemical synthesis method did not make a pure oxysilver nitrate product as has been reported previously. The solubility/stability of OSN and OSBS in water was examined, and it was determined that both OSN and OSBS decompose on contact with water with no sign of initial dissociation, but that OSBS does so much more rapidly than OSN. Stability of the two products under reaction conditions was also examined, and both products were determined to be reasonably stable under acidic/ozonation conditions. OSN demonstrated better thermal stability, as measured by DSC and thermogravimetric analysis (TGA). In addition, accelerated storage stability studies demonstrated that OSN could be stored with refrigeration, but that storage of OSBS without substantial product breakdown could not be achieved. OSC appeared to be the least stable material of the three. The inconsistent composition and poor stability of OSC have implications for the applications in which it is used, such as wound dressings.